Desenvolvimento de filmes nanoestruturados de polímeros condutores aplicados a sensores gustativos para avaliação de cafés - Paula, Gustavo Figueira de (2006)
This work aimed the investigation of ultra thin, polymeric film compositions made by the layer-by-layer deposition technique capable of coffee quality classification accordingly to stablished standards, using electrical impedance measurements and the statistical method Principal Component Analysis. Films made of polyaniline, poly(o-ethoxyaniline), polypyrrole, poly(3,4- ethylenedioxythiophene), poly(hexamethylene biguanide), poly(sodium methacrylate), fatty acids and derivatives, and other materials were studied. Films were grown showing the applicability of these materials to self-assembly of sensors based on polymeric materials. It was verified that PANI and DBSA has a great potential as materials for sensor construction by such process due to high rates of film growing. Itl was also observed that PEDOT(PSS) alternated with PHMB(HCl) was the better material combination for coffee evaluation. Impedance measurements in broad spectrum and use of variance-based ranking factors allowed selection of optimum operation frequency for each sensor, aiming the classification of brewed coffee by Global Quality and bean type. With this strategy, it was also possible to determine those materials that presented the best responses. Experimentally, it was shown that coffee deposition occurs on the electrode surface during the time of measurements, and proved that the usual washing procedure was not efficient to remove all adsorbed coffee compounds, being necessary the washing with detergents. The results of this work allows the construction of a sensor array to classify commercial coffees by Global Quality, and the optimization of a sensor array specialized on defective beans, which previously could not be determined on commercial samples of roasted coffees.